The Development Of E-Module Based On Discovery Learning In Theme 5 At Grade IV Elementary School - Putri, Dhara Atika; Desyandri, Desyandri; Adnan, Fachri; Fitria, Yanti (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
The research is attracted by students’ motivation to participate in learning. They only like using printed book materials and worksheets in schools through reading assignments and doing exercises in the book. It is developed by Discovery Learning-based e-modules in integrated thematic learning. It applies the ADDIE model. Data collection techniques use interview lists, validation sheets, questionnaires, and documentation. Data analysis techniques use descriptive techniques to describe validity, practicality, and effectiveness. The results showed that from the E-module feasibility test, the lecturers were subject matter experts, language expert lecturers, media/design expert lecturers, and one teacher. Based on the validation of material experts, it is obtained an average total score of 97% or classified as very valid. Then, the next validation shows valid criteria with an average score of 100% linguists. Design validation obtained a total average score of 95%, 94%, and an average score of 80%. One teacher tested the practicality of the E-module with a score of 98%. The student response test conducted on 13 grade IV students obtained a value with a proportion of 97%. E-modules in Discovery Learning-based thematic learning include features that are very practical or very feasible to use.